2022
DOI: 10.1186/s12912-022-00810-8
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led decision coaching by specialized nurses for healthy BRCA1/2 gene mutation carriers - adaptation and pilot testing of a curriculum for nurses: a qualitative study

Abstract: Background Women with BRCA1/2 mutations are at high risk to develop breast and ovarian cancer. To support these women to participate in shared decision-making, structured nurse-led decision coaching combined with an evidence-based decision aid may be employed. In preparation of the interprofessional randomized controlled trial to evaluate a decision coaching program to support preventive decisions of healthy female BRCA 1/2 gene mutation carriers (EDCP-BRCA), we adapted and pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…To meet with the multidisciplinary team approach, we developed a separate curriculum for specially trained nurses (Berger-Höger et al, 2022;Isselhard et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet with the multidisciplinary team approach, we developed a separate curriculum for specially trained nurses (Berger-Höger et al, 2022;Isselhard et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The growing satisfaction could also be due to the greater routine of the instructors and the growing competence of the participants during the training. To meet with the multidisciplinary team approach, we developed a separate curriculum for specially trained nurses (Berger‐Höger et al., 2022; Isselhard et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies (85%) reported the perspectives of HCPs who cared for individuals affected by hereditary breast and ovarian cancer (HBOC) [1,10,11,[20][21][22]24,26,[28][29][30], followed by one study focusing on Lynch syndrome [27], and one study focusing on various hereditary cancer syndromes [25]. Nine studies [1,10,11,20,22,24,25,28,29] examined the learning needs of HCPs regarding risk management and counseling for families with hereditary cancer (Table 2); eight studies [1,10,11,20,24,25,28,29] compared HCPs' learning needs according to their profession (Table 2); and six studies [10,21,22,26,27,30] explored the perspectives of HCPs on information that is essential for families with hereditary forms of cancer (Table 3). Decision-making process in their centers • [20] Optimal time to provide aid in making a decision • [25] Factors to consider when recommending risk management strategies…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Nine studies [1,10,11,20,22,24,25,28,29] examined the learning needs of HCPs regarding risk management and counseling for families with hereditary cancer (Table 2); eight studies [1,10,11,20,24,25,28,29] compared HCPs' learning needs according to their profession (Table 2); and six studies [10,21,22,26,27,30] explored the perspectives of HCPs on information that is essential for families with hereditary forms of cancer (Table 3). Decision-making process in their centers • [20] Optimal time to provide aid in making a decision • [25] Factors to consider when recommending risk management strategies…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…It has been shown that perceived control and reduction of psychological distress are eminent for comprehensive decision making [5, 66]. Several approaches to support medical counseling have been developed [67]. The implementation of digital health concepts could be useful for counselees as well as counseling physicians by tailoring individual information using low-threshold communication [68].…”
Section: Risk Management and Risk Communicationmentioning
confidence: 99%